Development of FlipaClip-Based Learning Media to Improve Problem-Solving Skills - Nifrani, Nila; Sutiarso, Sugeng; Firdaus, Rangga; Suningsih, Ari (Indonesian Journal of Mathematics Education, 2024)
This study aims to evaluate the effectiveness of FlipaClip as a learning media, and to compare the problem-solving abilities of students who learn using FlipaClip and PowerPoint. This study employed the ADDIE development paradigm (Analysis, Design, Development, Implementation, and Evaluate) as a framework for research and development (R&D). The findings demonstrated the validity and viability of learning media that use a contextual approach to linear program content. With extremely valid criteria, the material validation findings came out at 84.38%. The validation results from media experts were 94.79%, which is considered highly valid. Although the student response received an assessment percentage of 83.64%, the response also met the FlipaClip-based learning media's "very interesting" requirements, indicating that it is practical to use. Moreover, the research shows that FlipaClip-based learning media on program material can improve the mathematical problem-solving ability of class XI students. Quantitatively, the difference is shown by the interpretation of N-Gain obtained in the experimental class, which is quite an effective category with a percentage of 70.22%. The average mathematical problem-solving ability of grade XI students who are given FlipaClip-based learning media is higher than the average student who is not given the media, as indicated by the results of the independent sample t-test, namely the Sig. (2- tailed) value of 0.000 <0.05.